Integrated Safety and Process Economics Approach for Sustainable Process Design of Process Piping - Athar, M. (Springer, 2020)
Inherent safety is termed as the best approach of process safety which aids in creating sustainable process designs at the preliminary design stage. However, the available inherent safety techniques for process designs do not contemplate the nature of individual process equipment and process economics for the purpose. Consequently, an innovative approach is consolidated in this work to cover the gaps for the process piping, which is one of the most failing process equipment in the industry. The method consists of streams indexing section to identify critical pipes followed by risk estimation and analysis section to make the decision about safety for the critical process pipes. For unacceptable risk, the process conditions can be moderated as per the inherent safety concept. The critical process streams are analyzed again for risk acceptability and continued until the risk is acceptable. The use of inherent safety principle would change the process economics and can be compared with the base case to recognize the improvement. Conclusively, the resulted process design has the features of acceptable risk and enhanced process economics. Â© 2020, Springer Nature Singapore Pte Ltd.